The Effect of Food Safety on the Quality and Safety of Traditional Food Products at Noesaka Restaurant - Muhamad Rizki; Asep Parantika (Bogor Hospitality Journal, 2025)
Food safety is a condition of protecting food from biological and chemical contamination or anything that can damage, harm, or endanger human health. Therefore, practicing food safety in terms of the quality and safety of food served is very important for Noesaka Restaurant. This study aims to identify the factors causing food safety at Noesaka Restaurant, achieve proper hygiene measures, and improve food serving safety standards. Implement food safety according to standards. This study was conducted using a qualitative research approach using a qualitative descriptive method. The subjects of this study were an Executive Chef and Supervisor. This is an observation tour of food safety practices and activities at Noesaka Restaurant, to find out directly the existing problems. In addition to interviews and direct discussions based on research on food safety practices at Noesaka Restaurant, it can be concluded that the application of food safety principles has a significant impact on the quality and safety of food served. Among them are improving product quality, food safety, increasing consumer confidence, and compliance with food safety regulations. Overall, the consistent and effective implementation of food safety at Noesaka restaurants has a significant positive impact on food quality and safety, thus contributing to consumer satisfaction and safety.